Pengaruh Metode Pembelajaran Daring Terhadap Hasil Belajar Materi Operasi Hitung Bilangan Bulat - Akbar, La Ali; Nimreskosu, Fredrik; Syarifuddin3, Syarifuddin (INSTITUT AGAMA ISLAM NEGERI AMBON, 2023)
The purpose of this study was to determine the influence of online learning methods on the learning outcomes of number operation material in grade VI students of SD Negeri 64 Ambon. The research method used in this study was to use simple Regression analysis and t-Test with the help of the SPSS ver.16.0 application. The results showed that there was a significant influence between online learning methods on the learning outcomes of integer counting operation materials in students of SD Negeri 64 Ambon and the calculation of > ttabel at a real level of 0.05%, namely counting (3.463) and ttabel (2.119) and the amount of r value was 0.428 or 42.8%, namely the amount of contribution of online learning method factors to student learning outcomes on the meter of integer counting operations of grade VI students of SD Negeri 64 Ambon and 57.2%.influenced by other factors beyond the scope of the study. While the results of simple regression obtained a regression coefficient value of 0.645 that every increase in online learning methods by 1%, the learning outcomes of integer calculation operation materials for grade VI students of SD Negeri 64 also increased by 0.645. Keywords: Online Learning Methods, Learning Outcomes